1998
DOI: 10.1046/j.1365-2443.1998.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Human ubiquitin‐protein ligase Nedd4: expression, subcellular localization and selective interaction with ubiquitin‐conjugating enzymes

Abstract: Background: Nedd4 is a ubiquitin-protein ligase containing a calcium/lipid-binding domain, multiple WW domains and a C-terminal Hect domain, which is required for both the ubiquitin transfer and the association with E2 ubiquitin-conjugating enzymes. Nedd4 has been reported to be involved in the selective ubiquitination of some regulatory proteins in transcription and membrane transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 46 publications
5
77
0
2
Order By: Relevance
“…Ubiquitylation is best known for its role in the selective degradation and/or processing of intracellular proteins in eukaryotic cells [143]. In conjunction with a series of enzymes namely, E1, E2 and E3 ligases, ubiquitin is prepared for conjugation to other proteins in an ATPdependent manner [135,144].…”
Section: The Redistribution Of Paxillin Between the Membrane Ruffle Amentioning
confidence: 99%
See 2 more Smart Citations
“…Ubiquitylation is best known for its role in the selective degradation and/or processing of intracellular proteins in eukaryotic cells [143]. In conjunction with a series of enzymes namely, E1, E2 and E3 ligases, ubiquitin is prepared for conjugation to other proteins in an ATPdependent manner [135,144].…”
Section: The Redistribution Of Paxillin Between the Membrane Ruffle Amentioning
confidence: 99%
“…In conjunction with a series of enzymes namely, E1, E2 and E3 ligases, ubiquitin is prepared for conjugation to other proteins in an ATPdependent manner [135,144]. The conjugation of multiple ubiquitin molecules to a specific protein functions to target the protein for degradation by way of the 26S proteosomal pathway [143]. Consequently, like phosphorylation, ubiquitylation represents another post-translational modification that influences a wide variety of biological processes including, but not limited to gene expression, cellular stress response, antigen presentation, DNA repair, apoptosis, cell cycle and tumorigenesis [143,145].…”
Section: The Redistribution Of Paxillin Between the Membrane Ruffle Amentioning
confidence: 99%
See 1 more Smart Citation
“…This can occur as a consequence of direct mutation of PTEN gene itself and/or alteration of its degradation machinery, such as overexpression or superactivation of NEDD4-1. Indeed, it has been reported that NEDD4-1 expression level is very high in many human cancer cell lines (Anan et al, 1998), and it has also been documented to be highly overexpressed in a large cohort of human glioma samples (Oncomine database; Sun et al, 2006). Although the relationship of NEDD4-1 overexpression with PTEN in these gliomas is not clear, the important role of PTEN in gliomas warrants further investigation.…”
Section: Regulation Of Pten By Ubiquitinationmentioning
confidence: 99%
“…Permeases Gap1p and Fur4p are ubiquitylated at the cell membrane before being internalized by endocytosis (23)(24)(25). In addition, the human and mouse homologs of Rsp5, Nedd4, have been shown to be exclusively cytoplasmic (26,27). It will be interesting to determine the subcellular distribution of Rsp5.…”
Section: Fig 2 (A)mentioning
confidence: 99%